Use of Sahridayata in Conflict Resolution and Peace Building - Khatri, D.B. (Bodhi: An Interdisciplinary Journal, 2025)
This article deals with spiritual philosophy and its implication for conflict resolution and peace building in awakening astha chakras through physical and emotional dimensions of human body. Being empathetic, compassionate, cooperative and feeling equal to be oneness, can be defined as Sahridayata. The concept Sahridayata comes from the word ‘Saha’ means a quality characteristics or state of being and ‘hridaya’ refers to names a person of that faculty. So, etymologically Sahridaya refers to ‘one with a shared heart’ or ‘like hearted’. Similarly, Chakras are the energy centers of human body through which physical, mental and spiritual functions take place.